2012
DOI: 10.1002/meet.14504901305
|View full text |Cite
|
Sign up to set email alerts
|

Scientific bloggers under the altmetric microscope

Abstract: In this paper we present a preliminary altmetric study of scientific bloggers and how they use different social media (i.e. blogs, social bookmarking systems, and Twitter) for scholarly communication, information dissemination, and creation of visibility. We analyzed linking behavior in blog posts and tweets, number of comments assigned to blog posts and share of publications found in social bookmarking systems. Results show that heavy tweeting and blogging do not result in large numbers of followers and comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…We saw earlier that there are especially large differences between the samples' citation medians and other articles' citation medians for NEJM (Tables , ). Given the differences and the citation “boost” that NEJM articles receive when covered by the New York Times (Phillips et al., ), as well as bloggers linking to the New York Times (Peters et al., ), we decided to conduct a pilot study using the NEJM articles from the 2009 and 2010 samples. We “translated” first the medical terms to everyday language (e.g., sildenafil equals Viagra), then searched the Times web site and the news agency Reuters' web site for stories covering the research published by NEJM .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We saw earlier that there are especially large differences between the samples' citation medians and other articles' citation medians for NEJM (Tables , ). Given the differences and the citation “boost” that NEJM articles receive when covered by the New York Times (Phillips et al., ), as well as bloggers linking to the New York Times (Peters et al., ), we decided to conduct a pilot study using the NEJM articles from the 2009 and 2010 samples. We “translated” first the medical terms to everyday language (e.g., sildenafil equals Viagra), then searched the Times web site and the news agency Reuters' web site for stories covering the research published by NEJM .…”
Section: Resultsmentioning
confidence: 99%
“…A survey of SciLogs bloggers (a German blogging platform) showed that they were equally likely to have a post topic brought to their attention by the mainstream media as by scholarly publications (Puschmann & Mahrt, ). Looking at bloggers affiliated with research institutes from http://Scienceblogs.com and http://Scienceblogs.de, Peters, Beutelspacher, Maghferat, and Terliesner () found that bloggers often link to their own blogs or other blogs in their platform, to social media sites, and to major news sites such as Spiegel or the New York Times .…”
Section: Science and Research Blogsmentioning
confidence: 99%
“…The significance ascribed to alternative metrics for the evaluation of research fluctuates. While Haustein, Peters, Sugimoto, et al (2014) Even if there is no conclusive evidence of the significance of altmetrics for research evaluation, it is clear that research on and the use of altmetrics is becoming more and more popular and the (critical) discussions about possible application scenarios are increasing (Peters, Beutelspacher, Maghferat, & Terliesner, 2012). One gains the impression thereby that altmetrics is not a short-lived object of study in the information sciences, but is establishing itself as a new subfield .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, tweets are more likely to be retweeted when they contain links. This aspect has already been recognized by scholars and is now used for popularizing tweets with scientific content: Nearly a third of scientists' tweets contain URLs (Peters, Beutelspacher, Maghferat, & Terliesner, ), compared to only 22% for the general population of tweets (Boyd et al., ). According to Priem and Costello (), 6% of 2,322 tweets with URLs published by scientists forwarded users to scholarly publications, either directly or via different channels such as websites, while in Holmberg and Thelwall's () sample of scientists' tweets it was 2.2%.…”
Section: Introductionmentioning
confidence: 99%